2009
DOI: 10.1097/qai.0b013e31819118fa
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-Using HIV Type 1 Variants Are More Commonly Found in Peripheral Blood Mononuclear Cell DNA Than in Plasma RNA

Abstract: Mixtures of X4 and R5 sequences with highly divergent PSSM scores are present in both plasma and PBMC, but a shift toward a more abundant representation of X4-like PSSM scores in PBMC-derived DNA was apparent. Additional studies are needed to evaluate the clinical importance of these findings with regard to tropism prediction and the use of CCR5 antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
5
20
0
2
Order By: Relevance
“…On the other hand, correlations found between Trofile (ES) and bioinformatics algorithms in our study are similar to those found in other studies (6,16,18,19). In 8/10 (80%) patients genotyped from serum, proviral DNA, and virus isolates, the same tropism was predicted, supporting the absence of differences in the tropism among different viral sources (26). One of the discordant result sets was that for patient 2, for which genotypic approaches reported a D/M result in the virus isolate; however, the TROCAI result was clearly R5 (0% X4 and 100% R5) ( Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, correlations found between Trofile (ES) and bioinformatics algorithms in our study are similar to those found in other studies (6,16,18,19). In 8/10 (80%) patients genotyped from serum, proviral DNA, and virus isolates, the same tropism was predicted, supporting the absence of differences in the tropism among different viral sources (26). One of the discordant result sets was that for patient 2, for which genotypic approaches reported a D/M result in the virus isolate; however, the TROCAI result was clearly R5 (0% X4 and 100% R5) ( Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…The detection of the R5 variant in plasma and the X4 strain in PBMCs in the chronic phase of infection could represent the emergence of the most fit virus. A recent study suggested that CXCR4-using viruses were more frequent in PBMCs than in plasma samples from patients with advanced disease (49). However, the virus population during the first few months of HIV-1 infection is more homogenous than later in the disease evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Proviral DNA may be considered a potential alternative source of viral genetic material for tropism testing in patients with low or undetectable viral load. Cellular proviral DNA contains the reservoir of archived viruses, and it has been shown that V3 sequences predicted to derive from X4 viruses are present and even enriched in this reservoir [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Proviral DNA may be considered a potential alternative source of viral genetic material for tropism testing in patients with low or undetectable viral load. Cellular proviral DNA contains the reservoir of archived viruses, and it has been shown that V3 sequences predicted to derive from X4 viruses are present and even enriched in this reservoir [10][11][12].The aim of this study was to evaluate GTT on plasma RNA and proviral DNA for two groups of patients. The first group comprised treated and untreated patients with a viral load of 4500 copies/mL who underwent parallel testing of plasma RNA and proviral DNA.…”
mentioning
confidence: 99%